2020
DOI: 10.1111/1440-1681.13379
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy: Aetiology, pathophysiology and therapeutic interventions

Abstract: Cerebral palsy (CP) is the most common non‐progressive neurodevelopmental disorder in which the impairment of motor and posture functions occurs. This condition may be present in many different clinical spectra. Various aetiological and risk factors play a crucial role in the causation of CP. In various cases, the causes of CP may not be apparent. Interruption in the supply of oxygen to the fetus or brain asphyxia was considered to be the main causative factor explaining CP. Antenatal, perinatal, and postnatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 67 publications
0
26
0
3
Order By: Relevance
“…It is now well known that the prime risk factors for CP are delivery before 37 weeks and birth weight of less than 2.5 kg; however, there are some other problems evident in the literature which are found to be some of the prominent reasons for brain damage, some of which includes malformation of the brain in the developmental period, genetic causes, in utero mother and fetus infections, and various other issues [ 8 ]. Factors that may put the developing brain prone to injury were divided into risk factors that develop during preconception, during pregnancy, and after birth [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now well known that the prime risk factors for CP are delivery before 37 weeks and birth weight of less than 2.5 kg; however, there are some other problems evident in the literature which are found to be some of the prominent reasons for brain damage, some of which includes malformation of the brain in the developmental period, genetic causes, in utero mother and fetus infections, and various other issues [ 8 ]. Factors that may put the developing brain prone to injury were divided into risk factors that develop during preconception, during pregnancy, and after birth [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nearly 75% of CP occurs due to prenatal etiologies whereas 92% of causes are perinatal [ 2 , 12 ]. It is now well known that CP results from various reasons during pregnancy or during delivery, but in various studies, it is found that it occurs due to brain injury in the postneonatal period also [ 8 , 12 ]. Postnatal CP is defined as any trauma or disease in the brain after a neonatal period and before 5 years of age [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the average gain of 375 g in the kefir group during the 7 weeks of exposure to treatment represents a considerable benefit. It has also been reported an increase in the weight of infants diagnosed with the highest risk of neurological damage and treated with various probiotic species such as Bifidobacterium infantis , Streptococcus thermophilus , and Bifidobacterium lactis [ 24 , 25 ]. Garcia et al [ 44 ] found no significant differences in the weight of children with CP treated with pre-, pro-and synbiotics ( Lactobacillus reuteri DSM 17938 , and Agave inulin as a prebiotic).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have proven that the intake of probiotics reduces inflammation of the intestinal and respiratory mucosa, in addition to inducing other immunomodulatory properties [ 20 , 21 , 22 ]. To date, there have been few clinical trials that show an increase or improvement in weight or body mass index in children with CP that have been treated with probiotics, particularly children with a history of prematurity and poor neurological development [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%